Cytoskeletal lesions in anoxic myocardial injury. A conventional and high-voltage electron-microscopic and immunofluorescence study. - Ganote, C. E. (1987)
The role of cell swelling in mediating myocardial injury was studied in control (normoxic) and anoxic Langendorf perfused rat hearts. Control and 45-, 75-, or 90-minute anoxic hearts were exposed to hypotonic (200 mOsm/l) perfusion media to induce osmotic swelling. Anoxic hearts, but not control hearts, released myoglobin when subjected to osmotic swelling. Control hearts, exposed to hypotonic swelling, retained an intact cytoskeletal system of intermediate filaments, microfilaments and microtubules, intact sarcoplasmic reticulum, and intact sarcolemmal membranes. In contrast, swollen anoxic hearts showed a variety of ultrastructural lesions, including formation of large subsarcolemmal blebs associated with lysis of lateral Z-, M-, and A-band intermediate filament attachments, vesiculation of sarcoplasmic reticulum, and rupture of sarcolemmal membranes. Inter-mediate filament attachments with nuclear membranes were also broken, and microtubules disappeared from the perinuclear space. Sarcomere changes included distortion of Z bands, loss of lateral Z band-sarcolemmal attachments, and separations of myofibrils from internal faces in intercalated disks. Immunofluorescence studies of control hearts showed normal staining patterns for the cytoskeletal-associated proteins vinculin, alpha-actinin, and desmin. After 90 minutes of anoxia, hearts exhibited diminished staining of vinculin and alpha-actinin and relatively little change in desmin staining. The results demonstrate that a critical period of anoxia causes lesions in the cytoskeletal apparatus of myocardial cells which correlate with the increased osmotic fragility of irreversibly injured anoxic myocardial cells.